Gestión por procesos en la asociación de producción alimenticia procesamiento de plátano, snacks y bocaditos de Manabí (ASOPROAPLASBOMA) - Molina Vélez, Gipsy Nimia (2025)
This research aimed to implement process management to contribute to the improvement of the administrative management of the food production association for banana processing, snacks, and treats in Manabí, in order to enhance efficiency and productivity through a process manual. To carry out this research, three methodological phases were established: first, a diagnosis of the processes developed in the association was conducted, using descriptive analysis, application of thirteen characterization variables, and information gathering techniques such as interviews, process listing sheets, and an analysis of the current situation. Second, the association’s processes were structured by preparing process sheets describing the roles and activities of the selected processes; a process map was created to identify strategic, operational, and support processes; and flow diagrams were established. In the final phase, a properly structured process manual was developed as a proposal for the association. As a result of the research, a process management manual model was designed, adapted to the specific characteristics and needs of the association, with the purpose of organizing administrative management and improving productivity performance.